1991
DOI: 10.1111/j.1365-2230.1991.tb00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Lupus miliaris disseminatus faciei-report of a case in an elderly woman

Abstract: A 71-year-old Japanese woman developed red-brown to yellow papules symmetrically on the eyelids and cheeks. The histopathology of a papule showed caseation necrosis surrounded by epitheloid cells intermingled with giant cells in the dermis. The patient was thus diagnosed as lupus miliaris disseminatus faciei (LMDF). To the best of our knowledge, no LMDF patients of such an age have been described previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 1 publication
0
14
0
1
Order By: Relevance
“…265 Occasionally lesions occur elsewhere, including the axillae. 269,270 It has been suggested that as the currently used name is confusing, a new title should be substituted -FIGURE (facial idiopathic granulomas with regressive evolution). 268 This condition occurs in both sexes, predominantly in adolescents and young adults and rarely in the elderly.…”
Section: Lupus Miliaris Disseminatus Facieimentioning
confidence: 99%
“…265 Occasionally lesions occur elsewhere, including the axillae. 269,270 It has been suggested that as the currently used name is confusing, a new title should be substituted -FIGURE (facial idiopathic granulomas with regressive evolution). 268 This condition occurs in both sexes, predominantly in adolescents and young adults and rarely in the elderly.…”
Section: Lupus Miliaris Disseminatus Facieimentioning
confidence: 99%
“…A single case of LMDF without facial involvement has been reported 4 . LMDF is most often seen in young adults of both sexes, although cases have been reported among children 5 and the elderly 6 . Diascopy may reveal apple‐jelly nodules.…”
Section: Introductionmentioning
confidence: 99%
“…LMDF usually affects young adults of both sexes, but it has also been reported in children (8) and elderly patients (9,10). It typically presents with yellowishbrown dome-shaped papules and pustules localized in the central face, commonly involving the eyelids (1-3).…”
Section: Discussionmentioning
confidence: 99%